The Phage T4 Antiholin RI Has a Cleavable Signal Peptide, Not a SAR Domain - Mehner-Breitfeld, Denise; Schwarzkopf, Jan Michel Frederik; Young, Ry; Kondabagil, Kiran; Brüser, Thomas (Frontiers in Microbiology, 2021)
Holin/endolysin-mediated lysis of phage T4 of Escherichia coli is tightly regulated by the antiholins RI and RIII. While regulation by the cytoplasmic RIII plays a minor role, the periplasmic antiholin RI binds tightly to the holin T and is believed to directly sense periplasmic phage DNA from super-infections as a trigger for the inhibition of lysis. RI has been reported to contain a non-cleavable signal peptide that anchors the protein to the membrane. Lysis is believed to be induced at some stage by a membrane depolarization that causes a release of RI into the periplasm without cleavage of the signal anchor. For the current model of phage lysis induction, it is thus a fundamental assumption that the N-terminal TMD of RI is such a signal anchor release (SAR) domain. Here we show that, in contrast to previous reports, this domain of RI is a cleavable signal peptide. RI is processed and released into the periplasm as a mature protein, and inactivation of its signal peptidase cleavage site blocks processing and membrane-release. The signal peptide of RI can also mediate the normal translocation of a well-characterized Sec substrate, PhoA, into the periplasm. This simplifies the current view of phage lysis regulation and suggests a fundamentally different interpretation of the recently published structure of the soluble domains of the RI-T-complex.